Penerapan Pendekatan Differentiated Instruction dalam Peningkatan Kemampuan Penalaran Matematis Siswa SMA - Candra Ditasona (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
This research is based on the problem of low mathematical reasoning ability of high school students. This study aims to examine the improvement of mathematical reasoning ability among students who get Differentiated Instruction approach and conventional learning. The research design was quasi experiment with non-equivalent control group research design using Purposive Sampling technique. Instruments used include mathematical prior knowledge test, mathematical reasoning tests, observation sheets, and interview guides. Quantitative analysis was performed by using t-test and two-way anova test. The result of the research shows that (1) the improvement of student’s mathematical reasoning ability through DI learning is better than conventional learning, (2) The improvement of student’s mathematical reasoning ability through DI learning is better than the students who follow the conventional learning in terms of Mathematical Prior Knowledge. Keywords: Differentiated Instruction, Mathematical Prior Knowledge, Mathematical Reasoning.